Rural residential energy behaviour: a trans-generational and cross-country research - Ciprian-Ioan Rujescu; Andrea Feher; Cosmina-Simona Toader; Elena Claudia Sîrbulescu; Miroslav Raicov; Todor Marković; Željko Kokot (Environmental Research Communications)
Energy efficiency and consumption, sustainability and renewable energy sources are increasingly relevant topics in today’s world. Considering the increasing trend of energy use among household consumers in the context of the global energy deficit, the purpose of this study is to examine generational attitudinal variables of rural household consumers in Romania and the Republic of Serbia regarding the reduction of electricity consumption. It also studies the importance that household consumers assign to the use of ‘green’ energy in the energy mix, as a key factor for reducing the carbon footprint and sustainable development. The findings demonstrated some differences in the attitudes of respondents from the two analysed countries, corroborated with differences in sustainable behaviour between generations. The main results covering the whole analyzed sample show that the concern and interest in electricity consumption increases with the age of the respondents. Respondents from Generation X are the best informed about the knowledge of measures to reduce electricity consumption. The study reveals a higher degree of information and knowledge among respondents in the Republic of Serbia than in Romania regarding measures to reduce household electricity consumption and, at the same time, an increased interest in both countries for the use of renewable energy sources in the future. These findings highlight the complex dynamics of behavioural factors and their collective impact on attitudes related to sustainable electricity consumption. The study provides insights into how attitudinal variables influence different aspects of electricity consumption reduction behaviour, offering potential directions for interventions aimed at, on the one hand, promoting measures by which energy consumption can be reduced and on the other hand , encouraging the use of renewable energy in the energy system.